Analisis Perbandingan Kinerja Keuangan Sebelum Dan Sesudah Spin-Off Dengan Metode RGEC Studi Kasus BCA Syariah di Indonesia - Syawaluddin, Rizalul Muslih; Nurlaila, Nurlaila; Hasibuan, Nur Fadhilah Ahmad (Universitas Labuhanbatu, 2024)
This research aims to compare the financial performance of Bank BCA Syariah before and after the spin-off. This type of research is quantitative research with the data source used is secondary data. This research uses BCA Syariah bank annual financial report data for 2008-2021. The research sample is Bank BCA Syariah 2008-2021. Data processing and analysis techniques using Descriptive Statistical Analysis, Normality Test and Hypothesis Testing using Paired Sample T-Test and Wilcoxon Signed Rank Test. The program used for calculations uses SPSS version 25 and then the results from SPSS are interpreted. The research results show that there is a comparison of financial performance seen from the NPF, FDR, GCG, ROA and ROE variables before and after the spin-off at BCA Syariah 2008-2021.